If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 24z = 25 + 25z Add '-25' to each side of the equation. 25 + -25 + 24z = 25 + -25 + 25z Combine like terms: 25 + -25 = 0 0 + 24z = 25 + -25 + 25z 24z = 25 + -25 + 25z Combine like terms: 25 + -25 = 0 24z = 0 + 25z 24z = 25z Solving 24z = 25z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-25z' to each side of the equation. 24z + -25z = 25z + -25z Combine like terms: 24z + -25z = -1z -1z = 25z + -25z Combine like terms: 25z + -25z = 0 -1z = 0 Divide each side by '-1'. z = 0 Simplifying z = 0
| 60x-0.2x^2=p(x) | | 45+9y=90 | | -18=-3/5w | | 2v=-14/9 | | 6.5/3X+5=111/2 | | -3.9+m=-3.9 | | 2v=14/9 | | z^2-iz+12=0 | | 60-2P=-20+4P | | -7x=-3x-12 | | 3+7x=12-12x | | 14d+9=6d+25 | | 6(x-3)=-4.2 | | -2(-8u+3)-7u=5(u-1)-7 | | 8(a+1)=21.6 | | -43-3x=6-9x | | 33.7=9c-5 | | 3e-5=19.9 | | Y-23-37Y=3 | | p-18=18(h-6) | | 5x-14=16x | | p-18=23/3(h-6) | | 1x+34=26 | | 2x^2-12x+68=100 | | p=23/6h+18 | | 0=-4/5x-4 | | 7x+10=3x+78 | | -5t^2+40t+1.2=60 | | 5x+26=125-5x | | 24/34=4y+12/85 | | 45X^2+15X+5=0 | | 7/9=x/108 |